The role of aesthetics in the teaching and learning of data modelling. Issue 5 (24th March 2022) - Ferguson, Joseph Paul; Tytler, Russell; White, Peta
ABSTRACT: Reporting on a Grade 4 teaching and learning sequence, we highlight foundational constructs of measurement and data modelling which are fundamental to competence development in both science and mathematics. The sequence involved students generating and representing measures of their teacher's arm-span, with a focus on the invention and refinement of data representations characteristic of STEM epistemic practices. We undertook a micro-ethnographic practical epistemology analysis of video data of classroom and group discussions and student work, to explore the teaching and learning processes driving students' understandings of data variation and measures of central tendency. Through this analysis we appreciated aesthetic experiences as fundamental for students' growing epistemic and conceptual understandings and the teacher's pedagogical practices. We draw on the pragmatist aesthetic perspectives of Dewey and Peirce to show how students' sign-making shifted from an everyday interest in the arm span measuring process to an interest in the potentialities of the data set as an exploratory field. We consider this a shift from an everyday 'art' aesthetic to a 'mathematics' disciplinary aesthetic. We argue that such an aesthetic perspective, in which feeling and meaning are intertwined, provides a powerful way to understand the role of affect in learning.